Factors Affecting Business Environment for Investments: A Survey of Bahraini Businessmen - Kukreja, Gagan; Alshirawi, Ali Abdulla (Journal of Asian Business Strategy, 2014)
This research study will analyze the factors affecting business environment of Kingdom of Bahrain in the context of attracting investments, and how the government of Bahrain can attract more foreign direct investment (FDI) to the country. Furthermore, what are the facilities provided by government of Bahrain to enable investors to open new business and attract new investments. In this study, the perceptions of 80 local businessmen have been collected to know what they exactly expect from government and other stakeholders to invest further in businesses based in Bahrain. Based on the findings, recommendations have been provided for government and investors. This study aims to investigate the perception of decision makers of the for-profit organizations or market players. The wide-ranging functions of market selection criteria are examined to determine the most demanding contemporary issues. The selection approaches that business could consider while short listing the place of the next internationalization step and the mode of entry are reviewed in this research.